Improving Professional Competency Training for Teachers of SD Nasima Semarang Towards a Child-Friendly School: Pelatihan Peningkatan Kompetensi Profesional Guru SD Nasima Semarang Menuju Sekolah Ramah Anak - Yogi Swaraswati; Liftiah, Liftiah; Woro Apriliana Sari; Tri Esti Budiningsih; Moh. Iqbal Mabruri; Yuni Sulistyawati; Luthfi Atin Khusna (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service aims to improve professional competence towards a child-friendly school for SD Nasima's teachers in Semarang. The program was held on July 3, 2023, in the hall of SD Nasima Semarang. Forty-three teachers participated in it. The program's focus is to provide insight into the concept of child-friendly schools, skills in identifying problems and conducting assessments, and how to communicate effectively with parents regarding the special needs of students. This training was carried out in four sessions using methods in each session in the form of pre-test, post-test, group discussion, case analysis, and role play. The results of this training showed that 43 teachers (100%) felt that this activity met their expectations. As many as 33 teachers (77%) still hope there will be a follow-up to this program by providing more in-depth material so that teachers are more skilled in dealing with student-specific problems. Therefore, community service is its goal, namely to strengthen the professional competence of teachers in creating an educational environment that supports the development of students.